The Influence of Government, Enterprises, and the Public on the Security of Cross-border Data Flows and Optimization Strategies: An Information Ontological Perspective (Lex localis - Journal of Local Self-Government, 2025)
In the technology-driven era, the rapid advancement of information technologies, particularly artificial intelligence, has led to an increase in both the scale and complexity of data cross-border flows, thereby elevating data security to a global concern. This paper addresses the issue of data security in cross-border flows by reviewing pertinent literature, delineating the distinct phases of data cross-border flow development along with the challenges encountered at each stage, and introducing the public-private partnership (PPP) theoretical framework. A three-dimensional interactive theoretical framework centered on "government guidance, corporate impetus, and public engagement" is constructed to analyze the interaction mechanisms and influencing factors among government, enterprises, and the public. Based on this analysis, the paper proposes a series of targeted strategies to enhance the coordinated governance system for data cross-border flow security: refining the legal framework and regulatory approaches in policy and supervision; fostering innovation and standardization in technology and innovation; and boosting government credibility, enhancing public participation, and reinforcing interaction mechanisms in the realm of public trust and engagement. These measures aim to facilitate the transition of data cross-border flow security coordinated governance from theoretical discourse to practical application, effectively addressing various risks and challenges while promoting the healthy and orderly growth of the global digital economy.